Tuesday

March 31, 2015

March 31, 2015

Posted by **Scooby16** on Friday, September 23, 2011 at 6:37pm.

These functions have the property that f = f^-1(inverse) and g = g ^-1. That is, the inverse of f is equal to itself and the inverse of g is also equal to itself. Take the composition of each function with itself to show that this is true. Remember, if the function h(x) is equal to its own inverse, then h o h^-1 = x.

**Answer this Question**

**Related Questions**

Advanced Algebra - What is the inverse of each of the functions defined by the ...

Calculus-Inverse Functions - is the inverse function of x+ floor(x) equal to x...

Pre Calculus - Inverse functions what is the inverse function of f(x)=1/square ...

graph! - how can the graph of f(x)= X^2-4X be used to obtain the graph of y=g(x...

Pre-Calc - Does y=1/x have an inverse? It is a one-to-one function, so it should...

inverse - find f^-1 (x). (this is asking me to find the inverse) f(x) = -(x-2)^2...

Calculus (Derivatives of Inverse Functions) - Suppose f(x) = sin(pi cos(x)). On ...

Math - Find inverse of f if f(x)= x^2-4x+3, (for x is smaller than and equal to ...

Math - Inverse Functions - Find the inverses of the following functions. y = 3(x...

Algebra - what is the inverse of the linear parent function? How would you graph...